The Control of the Constitutionality of European Union Law by Means of Constitutional Complaints - Grądzka, Ilona (Review of European and Comparative Law, 2021)
The subject of this article is the institution of the constitutional complaint, which is analysed in connection with European integration. It should be noted that Poland’s membership of the European Union has had a great influence, not only on the system of national law, but also on the jurisprudence of the Polish Constitutional Tribunal; therefore considerations are carried out here mainly in relation to the Constitutional Tribunal. In examining the issue of the constitutional complaint, the following assumptions may be stated. First, the constitutional-complaint procedure, is in fact, the examination of the compliance of legal norms with the Constitution, any deviation being related to the entities initiating proceedings before the Constitutional Tribunal, Article 191(1)(6), of the Constitution[1], and to the material scope of the complaint, as determined in Article 79 of the Constitution. Second, there is no doubt that the constitutional complaint can become an important legal instrument shaping the jurisprudence of the Polish Constitutional Tribunal, which has to face constitutional issues related to European integration[2]. Following the example of the practice of other Member States, e.g. Germany, the Tribunal may use the institution of the constitutional complaint as a means of controlling the compliance of the secondary law of the European Union with the Constitution of the Republic of Poland. [1] The Constitution of the Republic of Poland, Journal of 2 April 1997, Journal of Law 1997, No. 78, item 483, as amended. [2] The literature on the subject indicates that the membership of nation States of the European Union obliges constitutional courts to act in the field of integration. Their task is to set the boundaries and conditions for the integration process. Jurisprudence in this area is referred to as acquis constitutionnel. Cf. Aleksandra Kustra, “Model skargi konstytucyjnej jako czynnik kształtujący orzecznictwo sądów konstytucyjnych w sprawach związanych z członkostwem państwa w Unii Europejskiej,” Państwo i Prawo, no. 3 (2015): 35.